Analyzing the drivers that shape people's perceptions of the impact of changes in forest cover and human population on water availability in the Mt. Elgon water tower - Kimbowa, George; Nanteza, Jamiat; Mfitumukiza, David; Ddumba, Saul Daniel; Nseka, Denis; Mugagga, Frank (Frontiers in Water, 2025)
Forest-water resource management often fails to deliver intended effects as farmers are limited to adopt agroforestry/sustainable land-use practices due to several barriers to uptake the scientifically proven and ecologically valuable land-use planning and management practices. It remains uncertain why it is difficult to align agroforestry campaigns with local interests despite numerous existing natural resource frameworks, policies, and management structures. In this study, we examined the potential of Q-methodology as a tool to analyze drivers of stakeholders' perceptions on the forest–water–people nexus (FWP-nexus) in relation to water availability and quality. The study was guided by a research question: What are the drivers of perception differences and/or similarities of scientists and local stakeholders on the FWP-nexus in relation to water availability in an agroforested landscape? For both Sipi River Sub-catchment and River Manafwa Sub-catchment, we discussed with diverse stakeholder groups. In each sub-catchment, stakeholders expressed their views on forest-water issues and possible management options and solutions. Together with stakeholders' groups, we used the generated information on forest-water issues in addition to relevant literature to develop a Q-set. The study compares the scientific insights and local stakeholders' perceptions on the FWP-nexus using the Q-methodology across the two sub-catchments. Study showed that perceptions of the FWP-nexus varied slightly among the two sub-catchments and among the upper and lower zones of the sub-catchments. From the two Sub-catchment comparison, the results indicate the significance of perceived importance of forests in increasing local rainfall and effect of local communities' involvement in planting trees on tree cover increase. The results indicate that issues surrounding the forest-water are majorly due to institutional failure other than farmers unwillingness to adopt sustainable agroforested landscape management practices and conforming to existing policies. There is need for: empowering and funding natural resource management departments to overcome institutional failure; adequate information on the performance assessment of agroforestry/tree growing projects; and developing and implementing the integrated management of forest/trees and water resources. For this study, the Q-methodology can guide in developing, testing, and documenting/communicating sustainable agroforested landscape management scenarios for water towers of mountainous regions. While comparative analysis across two sub-catchments strengthens robustness and reveals both shared and context-specific perceptions, the limited geographic scope may affect broader generalizability. Nonetheless, the results offer valuable guidance for inclusive land-use planning and spatially nuanced water governance.